حقوق المتهم دراسة مقارنة بين الشريعة الاسلامية والقانون الجزائري - جويحيف, عبد الله (جامعة الوادي university of eloued, 2014)
بنصوص الشريعة الاسلامية تناولت هده الدراسة مسألة المتهم في الشريعة الاسلامية وذلك عن طريق الوقوف على آراء فقهاء الاسلام في هده المسألة مع مقارنتها وتوصلت الدراسة الى تأكد سمو الشريعة الاسلامية و تميزها عن غبديرها من التشريعات والقوانين الوضعية حيث عنيت بالمتهم عناية فائقة ورغته رعاية تامة وأوضحت الضمانات المكفولة للمتهم في القانون الجزائري.This study deals with the rights of the accused ( defendant) in the Islamic Law ; that will be up to the Islamic scholars ‘views with the comparison to the Algerian Law. The study reaches the point to declare that the Islamic Law is higher and special that the other legislations and ordinance, it takes in high consideration the accused ( defendant) and gives much care. It shows also the guarantees given to him/ in the Algerian Law. But to mention the rights and guarantees in the constitution and the internal laws is not enough , we have to build the effective mechanisms to control seriously the real establishment of these guarantees. At the end, we conclude this study with the important results and recommendations
مقال
Keywords: الحقوق. المتهم. القانون الجزائري; Rights. Accused. Algerian law